CORRELATION BETWEEN MOTOR DIMENSIONS AND NEUROTICISM OF BOYS 7 TO 11 YEARS OF AGE - Maja Pori; Primož Pori (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The objective of this investigation was to establish the correlation between selected motor dimensions and personal dimension of neuroticism of children between seven and eleven years of age. The subject sample consisted of 92 schoolboys, attending the first five grades of the elementary school Kette-Murn in Ljubljana. Motor abilities were measured with a battery of 20 motor tasks (flexibility, speed, balance, strength and co-ordination) and neuroticism with the Big Five Questionnaire. The association between variables was analysed with correlation analysis. Personal dimension of neuroticism showed high correlation with the tests of coordination and speed in case of the children in lower classes and with the motor tests of flexibility in case of the children in higher classes of primary school.